African Group of Negotiators play major role in agricultural negotiations at COP18 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
COP17 in Durban gave agriculture a foothold within the United Nations Framework Convention on Climate Change (UNFCCC) negotiations, particularly through its Subsidiary Body for Scientific and Technological Advice (SBSTA). Building on this momentum, CCAFS East Africa helped create cohesion within the African Group of Negotiators (AGN) in order to facilitate a common position on agriculture within the negotiation process. In partnership with the African Climate Policy Centre (ACPC), the Common Market for Eastern and Southern Africa (COMESA), and the East African Community (EAC), CCAFS East Africa organized several post-Durban workshops to help articulate the African position and enhance capacity of the African Group of Negotiators.